Promoting Geoheritage Through a Field Based Geo-education Event, a Case Study of the Hungarian Geotope Day in the Bükk Region Geopark - László Sütő; Zsuzsanna Ésik; Roland Nagy; Erika Homoki; Tibor Novák; János Szepesi (Geoconservation Research)
Within the integrated network of protected geosites in nature conservation areas, nature trails have been established in Hungary since 1990. These trails play a major role in the organization of field-based geo-education activities. The Hungarian Geotope Day was established in the study area in 2009, based on the model of the German Geotope Day (Cserépfalu village, Bükk Region Geopark) where spectacular geological and geomorphological sites are included along the Devil's Tower Nature Trail. Field-based activities were organized through geology-themed hiking (“geohiking”) to expose geodiversity to the public. The number of the geotourists reached 1000 persons last year, but there was no detailed investigation about their motivation and segmentation. This preliminary work tries to explore the attitudes of the hiking geotourists with a questionnaire. The survey was conducted between 2016 and 2019. Questions ranged from basic social data through tourism motivation and some further development-related questions. Now, Geotope Day is nationwide and the number of locations exceeds 20 geosites. These results represent an important source of information for planning these outdoor educational activities.